Fullerenes(nC60) affect the growth and development of the sediment-dwelling invertebrate Chironomus riparius larvae. (November 2015) - Waissi-Leinonen, Greta C.; Nybom, Inna; Pakarinen, Kukka; Akkanen, Jarkko; Leppänen, Matti T.; Kukkonen, Jussi V.K.
Abstract: The possible toxicity of nanoparticles (NPs) to aquatic organisms needs to be investigated for chronic effects at low concentrations. Chronic effects of carbon NPs, fullerenesC60, on the midges of Chironomus riparius at different life stages on larvae and adult midges were investigated. Sediment associated fullerenesC60 were studied by 10-day growth and 42-day emergence tests with artificial sediment at nominal concentration ranges 0.0004–80 mg/kg dry weight. The body length decreased in the lower tested concentrations (0.0025–20 mg/kg), but the effect vanished with higher concentrations. Delayed emergence rate observed at 0.5 mg/kg. The observed effects correlated with analyzed sediment particle sizes indicating that small agglomerates of fullerene have more significant effects on C . riparius than larger agglomerates observed with higher C60 doses. The results reveal that fullerene may pose risks to benthic organisms, emerging as changes in the ecotoxic parameters studied here which inflects by the survival of the population. Graphical abstract: Highlights: Effects of fullerenesC60 to Chironomus riparius appeared at the low test concentration. A bell-shaped dose–response relationship occurred in growth patterns. Small fullerene aggregates have more significant effects on Chironomus riparius . Sediment particle size have significance correlation on growth parameters. Abstract : Low C60 concentrations lead conclusive effects on growth and reproduction of Chironomids.